К ИСТОРИИ ФОРМИРОВАНИЯ ГОРОДОВ И ГОРОДСКОГО НАСЕЛЕНИЯ КАРАКАЛПАКСТАНА В 1960-1970-е ГОДЫ (Scientific journal of the Fergana State University, 2023)
The article explores development of cities of Karakalpakstan in XX century. It is mentioned that the cities existed for the means of rural population and developel to satisfy their needs. In Karakalpakstan urbanization process development is related to migration of rural population, natural growth of population and climate conditions of the region